PERENCANAAN STRATEGI DALAM PELAKSANAAN PENGALIHAN KEWENANGAN PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN (PBB-P2) MENJADI PAJAK DAERAH DI KABUPATEN BANGKA PROVINSI KEPULAUAN BANGKA BELITUNG1 - Ramzi Ramzi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
on the text with the aim of achieving Syar'iah goodnes together and preserve the environment, the Qur'an gave spiritual information to people to be friendly to the earth, because the earth is a survival of humans and other living things, so in thiscase the law enforcement administration officials should be able to understand and apply these guidelines as a basis for environmental jurisprudence in law enforcement with the use of the instruments of administrative law, article writing isdone by using a normative-descriptive-analytical, and aimed to determine the guidelines for environmental jurisprudence in the perspective of law enforcement models using instruments